Shop theory - Anderson, James, 1905-; Tatro, Earl E.; Henry Ford Trade School (New York : McGraw-Hill, 1974)
An introductory textbook on machine shop theory and practice, including information on basic machine tools, bench operations, metrology, and career opportunities in the machine trades.
Includes bibliographical references and index.
Keywords: Machine-shop practice; Machine-tools.; Machine tools